Risky sexual behaviours among injection drugs users with high HIV prevalence: implications for STD control. (1st April 2002) - Tyndall, M W; Patrick, D; Spittal, P; Li, K; O'Shaughnessy, M V; Schechter, M T
Abstract : Injection drug use is inextricably linked to commercial sex work and the transmission of sexually transmitted disease (STD). In many communities prevention efforts have been stalled owing to the marginal existence of this community. This study describes the sexual activities, condom use, reported STDs, and commercial sex work in a large cohort of injection drug users. Seventy two per cent of male and 92% of female subjects in the cohort were sexually active. Among female subjects, 57% reported more than 100 lifetime partners. Condoms were generally not used with regular partners, used about half the time with casual partners, and used about 80% of the time with paying partners. Female sex workers were more likely to have unstable housing and to report incarceration in the previous six months. Reducing the transmission of STDs and HIV in drug using communities is a public health priority. While existing prevention programmes should be strengthened, innovative approaches to STD surveillance, diagnosis, and prevention are needed.